Mediation of Inventory Management in the Relationship Between Knowledge and Firm Performance - Aamir Rashid; Rizwana Rasheed (SAGE Open, 2023)
The role of inventory management is pivotal to improving the overall firm performance, but when it comes to the healthcare sector, then it becomes more crucial. This sector often countenances stocks-outs for life-saving drugs and equipment and competent staff that ascent the mortality rate. Thus, the current research aimed to analyze the effect of knowledge on firm performance through inventory management. For this research, a survey questionnaire with a deductive approach was utilized by collecting data from 200 respondents through multistage cluster sampling. IBM SPSS AMOS version 22.0 as a statistical tool was utilized to analyze the measurement model. Results of this research revealed a significant and positive mediation effect on the relationship between knowledge and firm performance. Finally, the results showed that the professionally well-equipped staff, accurate inventories, and stock availability improves the service quality and reduce the cost. Academicians, researchers, provincial healthcare ministries, state-funded organizations, and hospitals will all benefit from this research, which will also add to the current body of knowledge.